2015
DOI: 10.1111/hpb.12364
|View full text |Cite
|
Sign up to set email alerts
|

Does EUSFNA molecular analysis carry additional value when compared to cytology in the diagnosis of pancreatic cystic neoplasm? A systematic review

Abstract: k-ras mutational analysis used as an individual screening test has a poor diagnostic accuracy, as does cytology when used alone. The benefit comes with utilization in a combined fashion. More studies are needed to evaluate the correct sequence and utility of these tests for cyst differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 26 publications
(83 reference statements)
1
29
0
3
Order By: Relevance
“…11,12 In terms of molecular analyses for predicting malignancy in a mucinous cyst, there are currently insufficient data to warrant their usage in routine practice. 25,30,31 The cytologic recognition of high-grade atypia or worse in our study resulted in an overall sensitivity of 48.3% and an accuracy of 84.3% for detecting malignancy in pancreatic mucinous cysts. In comparison, at the threshold of a positive cytology diagnosis, the sensitivity and accuracy for detecting malignancy were 10.3% and 75.6%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…11,12 In terms of molecular analyses for predicting malignancy in a mucinous cyst, there are currently insufficient data to warrant their usage in routine practice. 25,30,31 The cytologic recognition of high-grade atypia or worse in our study resulted in an overall sensitivity of 48.3% and an accuracy of 84.3% for detecting malignancy in pancreatic mucinous cysts. In comparison, at the threshold of a positive cytology diagnosis, the sensitivity and accuracy for detecting malignancy were 10.3% and 75.6%, respectively.…”
Section: Discussionmentioning
confidence: 62%
“…Among them, endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) has become an important method of diagnosing pancreatic tumors due to its high safety, cost-effectiveness and accuracy (3,4). EUS-FNA demonstrates high sensitivity for histological diagnosis (75–94%) and a specificity approaching 100% in the majority of studies (5,6). However, false-negative, atypical and suspicious cytopathological diagnoses remain relatively frequent (5,7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of KRAS mutation analysis and CEA concentration measurements improved the diagnostic sensitivity of the latter alone from 67% to 84% for mucinous cysts . A recent systematic review of 12 articles showed that the combination of cytology and KRAS analysis was useful diagnostically (sensitivity, 71%; specificity, 88%), although KRAS mutational analysis alone had a poor diagnostic ability (sensitivity, 39%; specificity, 95%) . Singhi et al .…”
Section: Methodsmentioning
confidence: 99%
“…35 A recent systematic review of 12 articles showed that the combination of cytology and KRAS analysis was useful diagnostically (sensitivity, 71%; specificity, 88%), although KRAS mutational analysis alone had a poor diagnostic ability (sensitivity, 39%; specificity, 95%). 36 Singhi et al 37 evaluated 626 pancreatic cyst fluids obtained by EUS-FNA using next-generation sequencing and showed that the combination of KRAS/GNAS mutations and TP53/ PIK3CA/PTEN alternation analyses had a sensitivity of 89% and a specificity of 100% for diagnosing advanced neoplasia.…”
Section: Cyst Fluid Molecular Analysismentioning
confidence: 99%